Biochemical and cellular markers differentiate recovered, in‐line filtered plasma, and plasma obtained by apheresis methods. Issue 1 (10th June 2021) - Siekmann, Jürgen; Weber, Alfred; Bauer, Christoph; Turecek, Peter L.
Abstract: Background and Objectives: Assessment of plasma quality often focuses on the common safety tests for minimizing the risk of transmitting blood‐borne pathogens. Little attention is paid to the possible quality attributes that ensure a consistent biochemical composition of plasma for fractionation. We therefore investigated the suitability of selected biochemical and haematological attributes that could be used as markers of plasma quality obtained by different separation and pre‐treatment procedures. Material and Methods: We characterized six plasma types, including source plasma, plasma recovered by classic means and in‐line filtered plasma, by determining the analytical attributes protein content, coagulation factors and markers of coagulation, contact and complement activation. Residual cell content and cell‐specific variables were also measured. Results: We found relevant differences between the plasma types in complement activation, as indicated by C3a measurements, while thrombin antithrombin complex values and, to a minor extent, activated factor XII concentrations indicated only moderate differences in activation levels of coagulation and contact systems. The most striking differences, however, were detected in residual cell content and concentrations of the platelet‐associated proteins, platelet factor 4 and β‐thromboglobulin. We showed that leucocyte reduction filters disrupt cells. This includes platelets, thereby releasing the platelet‐associated proteins platelet factor 4 and β‐thromboglobulin, and leucocytes as demonstrated by the release of elastase from polymorphonuclear leucocytes. Furthermore, the filtration processing of whole blood can lead to activation of the complement system. Conclusion: Our results show that biochemical and cellular surrogate markers are valuable discriminators of plasma types.